Narrowing the diversification of supramolecular assemblies by preorganization. Issue 22 (26th February 2018) - Wang, Zhongyan; Liang, Chunhui; Shang, Yuna; He, Shuangshuang; Wang, Ling; Yang, Zhimou
Abstract : The preorganization of a precursor accelerates the formation of nanostructures with narrow diversification during EISA processes. Abstract : We designed and synthesized three phosphorylated peptides as precursors of the same peptide Nap-YYY. We found that different precursors led to different materials with almost identical chemical compositions at the final stages. Only Nap-YpYY could form very uniform nanofibers in a stable supramolecular hydrogel by enzyme-instructed self-assembly (EISA) at the physiological temperature (37 °C). In contrast, de-phosphorylation of the other two precursors (Nap-pYYY and Nap-YYpY) resulted in diverse nanostructures in metastable hydrogels with precipitates. The formation of uniform nanomaterials in the stable hydrogels was due to the preorganization property of the precursor Nap-YpYY, which facilitated rapid folding and accelerated the kinetics of hydrogelation of the resulting peptide Nap-YYY generated by the EISA process. Our study demonstrated the importance of the precursor for the self-assembly of nanomaterials and provided a useful strategy to manipulate them.